Neuroprotective activity of fullerenes: a literature review - Schopf, Patricia; Muraro, Pâmela; Cogo, Évelin; Volkmer, Tiago; Sagrillo, Michele; Zanella, Ivana (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
Fullerenes are the most studied carbon nanostructures in biological systems. Several works were carried out highlighting the properties of these structures, where its neuroprotective effect has been gaining prominence. In this context, this study aimed to do a literature review on the neuroprotective capacity of fullerenes and to discuss the main results found. The research was carried out in the Scielo database, where the descriptors used were “neuroprotection and fullerenes”. Based on the results found we can conclude that the neuroprotective effects of fullerenes are promising for the treatment of different dysfunctions in the central nervous system.